Low-platinum high-durability catalyst, preparation method and application thereof

CN123018007APending Publication Date: 2026-10-30WUXI WEIFU HIGH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611180604.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

1. 铂利用率低:传统碳载体(如 Vulcan XC-72)表面缺乏活性锚定位点,导致 Pt纳米颗粒易团聚(平均粒径>5nm),仅有不到 20% 的 Pt 原子参与催化反应,商业催化剂铂载量通常高达 20-70wt%,成本占电堆的 40% 以上;

Benefits of technology

(1)本发明的低铂高耐久催化剂,独特的介孔-微孔连续分级孔道结构提供了充足的负载位点,碳缺陷诱导铂纳米颗粒均匀成核生长,获得 2-3nm 的超小粒径,电化学活性面积可达 80-90m2/g Pt。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018007A_ABST
    Figure CN123018007A_ABST
Patent Text Reader

Abstract

The application relates to a low-platinum high-durability catalyst, belonging to the technical field of electrocatalytic materials of hydrogen fuel cells, and the low-platinum high-durability catalyst comprises a carbon carrier and platinum nanoparticles loaded on the carbon carrier, the carbon carrier is formed into a three-dimensional through mesoporous framework by taking silica nanospheres as a hard template, and is subjected to high-temperature selective etching treatment of carbon dioxide, hierarchical micropores and carbon topological defect sites are simultaneously constructed on the mesoporous pore wall surface, a mesopore-micropore continuous hierarchical pore channel structure is formed, and the mass fraction of the platinum nanoparticles in the catalyst is 10-20 wt%. The low-platinum high-durability catalyst has a unique mesopore-micropore continuous hierarchical pore channel structure, sufficient loading sites are provided, carbon defects induce uniform nucleation and growth of the platinum nanoparticles, an ultra-small particle size of 2-3 nm is obtained, and the electrochemical active area can reach 80-90 m 2 / g Pt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of hydrogen fuel cell electrocatalytic materials technology, and specifically discloses a low-platinum, high-durability catalyst and its preparation method. Background Technology

[0002] In the cathode reaction of proton exchange membrane fuel cells (PEMFCs), the slow oxygen reduction reaction (ORR) kinetics is a key factor limiting cell efficiency. Platinum (Pt)-based catalysts are currently the most effective ORR catalysts, but they face three major challenges: 1. Low platinum utilization: Traditional carbon supports (such as Vulcan XC-72) lack active anchoring sites on their surface, which makes Pt nanoparticles prone to agglomeration (average particle size > 5 nm). Only less than 20% of Pt atoms participate in the catalytic reaction. Commercial catalysts typically have a platinum loading of 20-70 wt%, accounting for more than 40% of the cost of the fuel cell stack. 2. Poor support stability: Under the high potential and acidic environment of fuel cell operation, carbon support is prone to oxidation and corrosion, causing Pt particles to fall off and resulting in rapid degradation of catalyst performance; 3. Poor stability of platinum particles: Platinum nanoparticles undergo Ostwald ripening, aggregation, and dissolution during long-term cycling, leading to a rapid decay of the electrochemically active surface area (ECSA).

[0003] In existing technologies, researchers have developed platinum alloys, core-shell structures, and heteroatom-doped carbon supports to reduce platinum usage and improve durability. However, platinum alloy catalysts suffer from core metal leaching, which can contaminate proton exchange membranes and poison catalytic sites. While heteroatom doping can enhance metal-support interactions to some extent, doped atoms are prone to loss under high temperatures and acidic environments, resulting in insufficient long-term stability. Core-shell structures have complex fabrication processes and difficult-to-control parameters, making large-scale industrial production difficult. Summary of the Invention

[0004] The purpose of this invention is to overcome the shortcomings of the existing technology and provide a low-platinum, high-durability catalyst, its preparation method and its application. Through a multi-scale control strategy of hierarchical pore construction, surface carbon defect engineering and precise anchoring of platinum particles, it achieves efficient synergy between the support and the active component without relying on heteroatom doping or transition metal alloying technology, and significantly improves ORR activity and stability under low platinum loading.

[0005] The technical solution adopted in this invention is: A low-platinum, high-durability catalyst includes a carbon support and platinum nanoparticles supported on the carbon support. The carbon support forms a three-dimensional interconnected mesoporous framework using silica nanospheres as a hard template and is subjected to high-temperature selective etching with carbon dioxide to simultaneously construct hierarchical micropores and carbon topological defect sites on the surface of the mesoporous pore walls, forming a continuous hierarchical pore structure of mesopores and micropores. The mass fraction of platinum nanoparticles in the catalyst is 10~20 wt%.

[0006] Preferably, the low-platinum, high-durability catalyst comprises mesopores with a diameter of 3–8 nm, wherein the mesopores and micropores are interconnected to form a three-dimensional network, and the micropores have a diameter of 0.5–2 nm, which are generated in situ by carbon dioxide etching onto the mesopore walls; the carbon support has a specific surface area of ​​1000–1800 m². 2 / g, pore volume 1.5~3.0 cm³ 3 / g; the carbon topological defect sites are distributed together with micropores, and the platinum nanoparticles are preferentially anchored on the carbon topological defect sites, with an average particle size of 1.5~3 nm.

[0007] A method for preparing a low-platinum, high-durability catalyst, comprising the following steps: Step S1. Preparation of monodisperse silica nanosphere template: Monodisperse SiO2 nanospheres are prepared and dispersed in a solvent to obtain a SiO2 nanosphere suspension; Step S2. Preparation of three-dimensional through-porous carbon precursor: Carbon source, oxalic acid and deionized water are mixed to prepare carbon source solution. SiO2 nanosphere suspension is mixed with carbon source solution, ultrasonically dispersed and solvent is evaporated to obtain dry gel. The dry gel is subjected to pre-carbonization and high-temperature carbonization treatment in an inert atmosphere to obtain SiO2 / carbon composite material. Step S3. Preparation of three-dimensional interconnected hierarchical mesoporous carbon: The SiO2 / carbon composite material is heated to 850~950℃ in an inert atmosphere and etched in carbon dioxide gas. Micropores and carbon topological defects are constructed simultaneously on the carbon skeleton surface. After cooling, the SiO2 template is removed, and the material is washed and dried to obtain three-dimensional interconnected hierarchical mesoporous carbon. Step S4. Defect-induced in-situ reduction of supported platinum nanoparticles: Three-dimensional interconnected hierarchical mesoporous carbon is dispersed in ethylene glycol to obtain a carbon dispersion, platinum salt solution is added and mixed evenly, the pH value of the system is adjusted to 8-9, reduction is performed, and the product is centrifuged, washed and vacuum dried to obtain a low-platinum, high-durability catalyst.

[0008] Preferably, in the method for preparing the low-platinum, high-durability catalyst, the particle size of the SiO2 nanospheres in step S1 is 3-8 nm, and the concentration of the SiO2 nanosphere suspension is 5-10 wt%.

[0009] Preferably, in the method for preparing the low-platinum, high-durability catalyst, the carbon source in step S2 is selected from one or more of sucrose, glucose, and phenolic resin, and the mass ratio of the carbon source to oxalic acid is 1:(0.02~0.05); the volume ratio of the SiO2 nanosphere suspension to the carbon source solution is 1:(1~2).

[0010] Preferably, in the method for preparing the low-platinum high-durability catalyst, the pre-carbonization temperature in step S2 is 350~450℃ and the time is 0.5~1.5 h; the high-temperature carbonization temperature is 900~1100℃ and the time is 2~4 h.

[0011] Preferably, in the preparation method of the low-platinum high-durability catalyst, the flow rate of carbon dioxide gas in step S3 is 50~100 mL / min, and the etching time is 1~3 h; the removal of the SiO2 template is specifically carried out by soaking in a 10 wt% hydrofluoric acid solution to remove the SiO2 template.

[0012] Preferably, in the method for preparing the low-platinum, high-durability catalyst, the platinum salt in step S4 is selected from chloroplatinic acid, potassium chloroplatinate, and platinum acetylacetonate; the concentration of the carbon dispersion is 6-10 mg / mL.

[0013] Preferably, in the method for preparing the low-platinum, high-durability catalyst, the reduction temperature in step S4 is 120-140°C and the reduction time is 2-4 h.

[0014] Application of a low-platinum, high-durability catalyst, wherein the low-platinum, high-durability catalyst is used in the oxygen reduction reaction at the cathode of a proton exchange membrane fuel cell.

[0015] The present invention has the following advantages: (1) The low-platinum, high-durability catalyst of the present invention has a unique mesoporous-microporous continuous hierarchical pore structure that provides sufficient loading sites. Carbon defects induce uniform nucleation and growth of platinum nanoparticles, resulting in an ultra-small particle size of 2-3 nm and an electrochemical active area of ​​80-90 nm. 2 / g Pt.

[0016] (2) The preparation method of the low platinum high durability catalyst of the present invention forms a strong Pt-C covalent bond between carbon defects and platinum atoms, which increases the platinum dissolution barrier by more than 30%, effectively inhibiting the agglomeration, dissolution and migration of platinum particles. After 30,000 accelerated aging cycles, the ECSA retention rate is still more than 80%.

[0017] (3) The preparation method of the low platinum high durability catalyst of the present invention uses a hard template method combined with carbon dioxide in-situ etching to prepare a carbon support, and uses a defect-induced in-situ reduction method to load platinum nanoparticles. The whole process does not require complex equipment, the parameters are easy to control, the repeatability is good, and it is suitable for large-scale industrial production. Attached Figure Description

[0018] Figure 1 is a schematic diagram of the three-dimensional interconnected hierarchical mesoporous carbon-supported platinum nanoparticles of the present invention.

[0019] Figure 2 shows the CV cyclic voltammetry curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 of this invention.

[0020] Figure 3 shows the LSV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 of this invention.

[0021] Figure 4 shows the CV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 before and after 30,000 square wave cycles.

[0022] Figure 5 shows the LSV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 before and after 30,000 square wave cycles. Detailed Implementation

[0023] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments; unless otherwise stated, the terminology used herein should be understood in accordance with the conventional usage of those skilled in the art.

[0024] Example 1 A low-platinum, high-durability catalyst includes a carbon support and platinum nanoparticles supported on the carbon support. The carbon support forms a three-dimensional interconnected mesoporous framework using silica nanospheres as a hard template and is subjected to high-temperature selective etching with carbon dioxide to simultaneously construct hierarchical micropores and carbon topological defect sites on the surface of the mesoporous pore walls, forming a continuous hierarchical pore structure of mesopores and micropores. The mass fraction of platinum nanoparticles in the catalyst is 20 wt%.

[0025] The mesopores have a diameter of 3–8 nm, and the mesopores and micropores are interconnected to form a three-dimensional network. The micropores have a diameter of 0.5–2 nm and are formed in situ by etching carbon dioxide onto the walls of the mesopores. The specific surface area of ​​the carbon support is 1000–1800 m². 2 / g, pore volume 1.5~3.0 cm³ 3 / g; the carbon topological defect sites are distributed together with micropores, and the platinum nanoparticles are preferentially anchored on the carbon topological defect sites, with an average particle size of 2.1 nm.

[0026] A method for preparing a low-platinum, high-durability catalyst, comprising the following steps: Step S1. Preparation of monodisperse silica nanosphere template: Monodisperse SiO2 nanospheres are prepared and dispersed in a solvent to obtain a SiO2 nanosphere suspension; Step S1 is as follows: 9 mL of tetraethyl orthosilicate is added to 100 mL of ethanol and stirred evenly. Then, 10 mL of ammonia (25 wt%) and 5 mL of deionized water are added and stirred at 25 °C for 6 h to obtain a monodisperse SiO2 nanosphere suspension with a particle size of about 5 nm.

[0027] Step S2. Preparation of three-dimensional through-porous carbon precursor: 10g sucrose, 0.3g oxalic acid and 80mL deionized water were mixed to prepare a carbon source solution. 50mL SiO2 nanosphere suspension (containing 5g SiO2) was mixed with 50mL carbon source solution. After ultrasonic dispersion for 40min, the solvent was evaporated at 70℃ to obtain a dry gel. The dry gel was pre-carbonized at 400℃ for 1h under nitrogen atmosphere, and then heated to 1000℃ for 3h. After natural cooling to room temperature, SiO2 / carbon composite material was obtained. Step S3. Preparation of three-dimensional interconnected hierarchical mesoporous carbon: The SiO2 / carbon composite material was heated to 900℃ in an argon atmosphere and etched in carbon dioxide gas (flow rate 80mL / min) for 2 hours, then naturally cooled to room temperature. The etched product was soaked in 10wt% hydrofluoric acid solution for 24 hours to completely remove the SiO2 template, then washed with deionized water until neutral, and vacuum dried at 100℃ for 12 hours to obtain three-dimensional interconnected hierarchical mesoporous carbon. The specific surface area of ​​this carbon support was measured to be 1560m². 2 / g, pore volume 2.2cm 3 / g, with mesopores having a diameter of approximately 5nm and micropores having a diameter of approximately 1.2nm; Step S4. Defect-induced in-situ reduction of supported platinum nanoparticles: 0.8 g of three-dimensional interconnected hierarchical mesoporous carbon was dispersed in 100 mL of ethylene glycol to obtain a carbon dispersion. A solution containing 5.26 mL of chloroplatinic acid in ethylene glycol was added and ultrasonically dispersed for 30 min until homogeneous. The pH of the system was adjusted to 8.5. The pH of the mixture was then adjusted to 8.5 with 0.1 mol / L sodium hydroxide solution. The mixture was transferred to an oil bath and heated at 130 °C for 3 h for reduction. The product was centrifuged, washed several times with ethanol and deionized water, and vacuum dried at 60 °C for 12 h to obtain a 20 wt% Pt / three-dimensional interconnected hierarchical mesoporous carbon catalyst.

[0028] ICP testing showed that the mass fraction of platinum in the catalyst was 19.1 wt%; XRD testing showed that the average particle size of the platinum nanoparticles was approximately 2.1 nm, and they were uniformly dispersed on the inner wall of the mesoporous channels without obvious agglomeration.

[0029] Example 2 20 wt% Pt / Three-dimensional interconnected hierarchical mesoporous carbon catalyst The difference between this embodiment and Embodiment 1 is that the carbon dioxide etching time in step S3 is 1.5 hours, resulting in a carbon support with a specific surface area of ​​1320 m². 2 / g, pore volume 1.9cm 3 / g, the final catalyst has a platinum mass fraction of 19.3%, and the average particle size of platinum nanoparticles is about 2.4nm.

[0030] Comparative Example 1: Commercial Pt / C catalyst (Johnson & Johnson, 20 wt% platinum) The catalysts prepared in Examples 1-3 were electrochemically tested using a three-electrode system. The working electrode was a glassy carbon electrode (5 mm in diameter) with the catalyst supported, the counter electrode was a platinum sheet, the reference electrode was a reversible hydrogen electrode (RHE), and the electrolyte was a 0.1 mol / L perchloric acid solution. Before testing, nitrogen gas was purged into the electrolyte for 30 min to remove oxygen. Cyclic voltammetry (CV) scans were then performed in the potential range of 0.05–1.0 V (V vs. RHE) at a scan rate of 20 mV / s until the curve stabilized. The ORR performance was tested using linear sweep voltammetry (LSV) in the potential range of 0.2–1.2 V (V vs. RHE) at a scan rate of 20 mV / s and a rotation speed of 1600 rpm.

[0031] Durability testing employed accelerated aging test (ADT). Before the square wave test, the CV and LSV were first tested at a sweep rate of 20 mV / s to facilitate the calculation of initial performance. The square wave test was conducted within the potential range of 0.6 V and 0.95 V (V vs. RHE). The two test voltages were held for 3 seconds, and a test cycle was completed in 6 seconds. After 30,000 cycles, the ORR performance and electrochemical active area were tested again.

[0032] Comparative Analysis of Examples: By comparing Examples 1 and 2, it can be seen that as the CO2 etching time is extended from 1.5h to 2h, the specific surface area of ​​the carbon support increases from 1320m2 / g to 1560m2 / g, and the pore volume increases from 1.9cm3 / g to 2.2cm3 / g. Correspondingly, the average particle size of platinum nanoparticles decreases from 2.4nm to 2.1nm. This is because the extended etching time increases the number of micropores and defects generated on the carbon surface, providing more nucleation sites for platinum particles, enabling the platinum particles to be more uniformly dispersed and grow to a smaller size. The test results are shown in Table 1.

[0033] Table 1. Electrochemical performance test results of different catalysts The meanings of the key performance parameters in Table 1 are as follows: Half-wave potential is the core indicator for measuring the catalytic activity of ORR. The higher the potential, the better the catalyst activity; Mass activity (MA) refers to the catalytic current per unit mass of platinum, which directly reflects the utilization efficiency of platinum; Electrochemical active area (ECSA) refers to the effective area of ​​platinum on the catalyst surface that can participate in the electrochemical reaction; ECSA retention rate refers to the ratio of ECSA after accelerated aging test to the initial ECSA, which reflects the durability of the catalyst. The higher the retention rate, the better the durability.

[0034] The test results in Table 1 show that: Initial activity: The half-wave potential of Example 1 reached 0.91V, which is 14mV higher than the 0.896V of the comparative commercial Pt / C; the mass activity reached 0.25A / mgPt, an improvement of 45.3% compared to the comparative example; and the electrochemical active area reached 88.47m². 2 / g, which is also higher than the comparative example's 80.33m. 2 / g indicates that the catalyst of the present invention has significantly higher initial ORR activity, mainly due to the efficient material transport channels and more active sites provided by the three-dimensional through-type hierarchical pore structure, as well as the smaller particle size and higher specific surface area utilization resulting from the uniform dispersion of platinum particles induced by carbon defects.

[0035] Durability: After 30,000 cycles of accelerated aging test, the ECSA retention rate of Example 1 was as high as 83.24%, which was much higher than the 62.12% of the comparative example; the half-wave potential decreased by only 10mV, while that of the comparative example decreased by 16mV; the mass activity retention rate reached 80%, while that of the comparative example was only 61%. This fully demonstrates that the catalyst of the present invention has excellent durability. The reason is that the strong anchoring effect of carbon defects on platinum particles effectively inhibits the migration and agglomeration of platinum particles. At the same time, high-temperature carbonization and CO2 etching improve the graphitization degree and corrosion resistance of carbon support, and the hierarchical pore structure also buffers the volume change of platinum particles during cycling.

[0036] Figure 2 shows the cyclic voltammetry (CV) curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 of this invention. In the CV curves, the area of ​​the hydrogen adsorption-desorption peak in the potential range of 0.05-0.4V is proportional to the electrochemically active area of ​​the catalyst. The larger the peak area, the higher the ECSA. As can be seen from the figure, the hydrogen adsorption-desorption peak area of ​​Example 1 is the largest, followed by Example 2, and the comparative example is the smallest. This is completely consistent with the ECSA data in Table 1.

[0037] Figure 3 shows the LSV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 of this invention. In the LSV curves, the closer the curve is to the upper left, the higher the half-wave potential, indicating that the catalyst has better ORR activity. It can be clearly seen from the figure that the LSV curve of Example 1 is at the top, followed by Example 2, and the comparative example is at the bottom, which intuitively shows the activity advantage of the catalyst of this invention compared with commercial Pt / C.

[0038] Figure 4 shows the CV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 before and after 30,000 square wave cycles. Comparing the CV curves before and after cycling, it can be seen that the CV curves of Examples 1 and 2 of this invention change very little, and the hydrogen adsorption and desorption peak area decreases only slightly; while the CV curve of the comparative example commercial Pt / C changes significantly, and the hydrogen adsorption and desorption peak area decreases significantly, indicating that its electrochemical active area is severely lost.

[0039] Figure 5 shows the LSV curves of the catalysts prepared in Examples 1-2 and Comparative Example 1 before and after 30,000 square wave cycles. Comparing the LSV curves before and after cycling, it can be seen that the LSV curves of Examples 1 and 2 of the present invention show almost no significant shift, and the half-wave potential decreases very little; while the LSV curve of the commercial Pt / C in the comparative example shows a significant shift, and the half-wave potential decreases significantly, further demonstrating that the catalyst of the present invention has excellent long-term operational stability.

[0040] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A low-platinum, high-durability catalyst, characterized in that, The catalyst includes a carbon support and platinum nanoparticles loaded on the carbon support. The carbon support forms a three-dimensional through-pore framework with silica nanospheres as a hard template and is subjected to high-temperature selective etching with carbon dioxide to simultaneously construct hierarchical micropores and carbon topological defect sites on the surface of the mesopore walls, forming a continuous hierarchical pore structure of mesopore-micropore. The mass fraction of platinum nanoparticles in the catalyst is 10~20 wt%.

2. The low-platinum, high-durability catalyst according to claim 1, characterized in that, The mesopores have a diameter of 3–8 nm, and the mesopores and micropores are interconnected to form a three-dimensional network. The micropores have a diameter of 0.5–2 nm and are generated in situ by etching carbon dioxide onto the walls of the mesopores. The specific surface area of ​​the carbon support is 1000–1800 m². 2 / g, pore volume 1.5~3.0 cm³ 3 / g; the carbon topological defect sites are distributed together with micropores, and the platinum nanoparticles are preferentially anchored on the carbon topological defect sites, with an average particle size of 1.5~3 nm.

3. A method for preparing a low-platinum, high-durability catalyst, characterized in that, Includes the following steps: Step S1. Preparation of monodisperse silica nanosphere template: Monodisperse SiO2 nanospheres are prepared and dispersed in a solvent to obtain a SiO2 nanosphere suspension; Step S2. Preparation of three-dimensional through-porous carbon precursor: Carbon source, oxalic acid and deionized water are mixed to prepare carbon source solution. SiO2 nanosphere suspension is mixed with carbon source solution, ultrasonically dispersed and solvent is evaporated to obtain dry gel. The dry gel is subjected to pre-carbonization and high-temperature carbonization treatment in an inert atmosphere to obtain SiO2 / carbon composite material. Step S3. Preparation of three-dimensional interconnected hierarchical mesoporous carbon: The SiO2 / carbon composite material is heated to 850~950℃ in an inert atmosphere and etched in carbon dioxide gas. Micropores and carbon topological defects are constructed simultaneously on the carbon skeleton surface. After cooling, the SiO2 template is removed, and the material is washed and dried to obtain three-dimensional interconnected hierarchical mesoporous carbon. Step S4. Defect-induced in-situ reduction of supported platinum nanoparticles: Three-dimensional interconnected hierarchical mesoporous carbon is dispersed in ethylene glycol to obtain a carbon dispersion, platinum salt solution is added and mixed evenly, the pH value of the system is adjusted to 8-9, reduction is performed, and the product is centrifuged, washed and vacuum dried to obtain a low-platinum, high-durability catalyst.

4. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S1, the particle size of the SiO2 nanospheres is 3~8 nm, and the concentration of the SiO2 nanosphere suspension is 5~10 wt%.

5. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S2, the carbon source is selected from one or more of sucrose, glucose, and phenolic resin, and the mass ratio of carbon source to oxalic acid is 1:0.02~0.05; the volume ratio of SiO2 nanosphere suspension to carbon source solution is 1:1~2.

6. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S2, the pre-carbonization temperature is 350~450℃ and the time is 0.5~1.5 h; the high-temperature carbonization temperature is 900~1100℃ and the time is 2~4 h.

7. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S3, the flow rate of carbon dioxide gas is 50~100 mL / min, and the etching time is 1~3 h; the SiO2 template is removed by soaking in a 10 wt% hydrofluoric acid solution.

8. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S4, the platinum salt is selected from one of chloroplatinic acid, potassium chloroplatinate, and platinum acetylacetonate; the concentration of the carbon dispersion is 6~10 mg / mL.

9. The method for preparing the low-platinum, high-durability catalyst according to claim 3, characterized in that, In step S4, the reduction temperature is 120~140℃ and the reduction time is 2~4 h.

10. The application of a low-platinum, high-durability catalyst according to any one of claims 1-2, characterized in that, Low-platinum, high-durability catalysts are used in the oxygen reduction reaction at the cathode of proton exchange membrane fuel cells.